Reviews of Environmental Contamination and Toxicology - Whitacre, David M.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
Forward Preface Aquatic Toxicology of Perfluorinated Chemicals John P. Giesy, Jonathan E. Naile, Jong Seong Khim, Paul D. Jones, and John L. Newsted Occurence and Fat of Human Pharmaceuticals in the Environment Sara C Monteiro and Alistair BA Boxall Chemistry and Environmental Fate of Fenoxycarb Jonathan J Sullivan Index
Aquatic Toxicology of Perfluorinated Chemicals -- Occurrence and Fate of Human Pharmaceuticals in the Environment -- Chemistry and Environmental Fate of Fenoxycarb.
Keywords: Environmental sciences; Environmental management; Environmental toxicology; Waste disposal; Environment; Environmental Management; Ecotoxicology; Waste Management/Waste Technology